Taxonomic revision of the genus Reseda L. (Resedaceae) in Turkey - Çi̇lden, Emre; Yildirimli, Şi̇nasi̇ (Phytotaxa, 2020)
Taxonomical studies on the genus Reseda in Turkey were first undertaken as part of the revisionary work of Flora of Turkey. Although several successive updates were published in recent times, Reseda has not yet been studied in detail after that valuable previous work. In this context, the present contribution reports a revision of Reseda taxa occurring in Turkey. Eighteen taxa (species, subspecies and varieties) are accepted, ten of which are endemic to the country. Three species, R. balansae, R. saadae and R. coodei, are rediscovered respectively after 159, 126 and 49 years since their first collections, and the new combination R. germanicopolitana var. glabra (Karavel. & Vural) Çilden is established. A new identification key is provided to facilitate further identification. Morphological descriptions are updated, and illustrations and photographs are provided for all species. Types are indicated for all accepted names, of which one lectotype and a second-step lectotype are designated here.